2015
DOI: 10.1111/avsc.12138
|View full text |Cite
|
Sign up to set email alerts
|

Nature will have its way: local vegetation trumps restoration treatments in semi‐natural grassland

Abstract: Questions: How do various grassland restoration methods (hay transfer from local or distant donors, seed sowing or natural regeneration) perform in restoration of species-rich, semi-natural grasslands? Are any of the donors particularly well suited as reference vegetation? Do bare soil treatments give better results than treatments where the soil is covered? What are the probabilities of steering vegetation development towards donor vegetation under the various restoration treatments?Location: Sunnfjord open-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…Although this process is most distinct in studies employing small plots, it has also been observed in in situ restoration experiments using larger plots (Lepš et al ; Baasch et al ). Colonization by natural dispersal is actually regarded as an inherent (and beneficial) property of natural regeneration (Conrad & Tischew ), given sufficient seed sources and connectivity between restoration areas and grasslands in the surrounding landscape (Auestad et al ). Our results indicate that natural regeneration may be regarded as a successful and economically favorable restoration method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this process is most distinct in studies employing small plots, it has also been observed in in situ restoration experiments using larger plots (Lepš et al ; Baasch et al ). Colonization by natural dispersal is actually regarded as an inherent (and beneficial) property of natural regeneration (Conrad & Tischew ), given sufficient seed sources and connectivity between restoration areas and grasslands in the surrounding landscape (Auestad et al ). Our results indicate that natural regeneration may be regarded as a successful and economically favorable restoration method.…”
Section: Discussionmentioning
confidence: 99%
“…Plant material may be transferred as hay from local sources (Kiehl et al ; Rydgren et al ) or as site‐specific seed mixtures of local origin. Using the latter makes it possible to tailor vegetation to include particular target species or to meet aesthetic requirements (Rydgren et al ; Auestad et al ). The species in local seed mixtures also serve as target species for the restoration as they are deliberately selected to increase species richness and support local seminatural grassland vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers working on similar timescales have documented that different seed sources can generate differences in plant communities (Baasch et al 2012;Auestad et al 2015), and that soil amendments like those used here can jump-start improvements in soil quality (Tandy et al 2009;Oldfield et al 2014;Emam 2015) and affect plant community composition (Paschke et al 2005). However, few, if any, have connected multiple soil amendment types to plant communities on this timescale.…”
Section: Discussionmentioning
confidence: 84%
“…Regardless of restoration measure, it is important to evaluate restoration outcomes, especially in long-term follow-up studies. Short-term studies may reveal temporary trends, but the results might not be stable over time [ 18 , 87 ]. In this study, the species richness and density in the restored grasslands did not resemble reference conditions even after 12–20 years, while composition including all species as well as grassland specialists was similar.…”
Section: Discussionmentioning
confidence: 99%